Improvement of Maize Growth and Production through a Combination of Leaf Defoliation and SP-36 Dosage in a Close Cropping System - Galushasti, Andarula; Ningtyas, Dini Putri; Jumiatun, Jumiatun; Mukhlisin, Ilham (Agro Bali : Agricultural Journal, 2024)
The high demand for Maize encourages various agricultural innovations. The study aims to examine the effect of defoliation and P fertilizer application on the growth and production of the Madura 3 Maize variety which is grown in the close cropping system. This study used a randomized block design consisting of two factors with three replications. The parameters observed were stem diameter, root weight, cob fresh weight, cob dry weight, dry seed weight, and 100 seed weight. The results showed that there was a significant interaction between the defoliation factor and the dose of SP-36 on cob diameter, where the highest diameter (4,75 cm) was found in the combination of non-defoliation and SP-36 150 kg.ha-1. Overall, the non-defoliation of an SP-36 of 250 kg.ha-1 showed the best result on Maize growth and production. The addition of the dose of SP-36 also needs to pay attention to the needs of plants.